EKSTRAK ETANOL DAUN SIRIH MERAH (Piper crocatum) MENURUNKAN KADAR GULA DARAH MENCIT DIABETES - Ambali Azwar Siregar; Urip Harahap; Mardianto Mardianto (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Diabetes mellitus is one of desease that have a large population and trend to increase. sulfonylurea and biguanide are almost used treatment but have unexpected side effects. The research still necessary to seek alternative medicine, such as Piper crocatum.This study aimed to determine the effect of ethanol extract of red betel leaves on blood sugar levels and body weight of mice (Mus musculus L.) diabetes. This riset was started to produce simplicia and drilled become powders, continued extract with 70% ethanol. The extract was evaporated with rotary evaporator until obtaine crude extract. And then screen it that determine phytochemical. To continued test on tolerance of level of glucose then mice diabetes induced aloxan.In summary, extract of red betle ethanolic has contained alkaloid, quercetin flavonoid, steroid and fenolic compounds and decreased level of glucose in blood mice diabetes. Besides, it can reduce lose of weight symptom.